Fiscal decentralization effect on economic growth in Bali - Manggar Wulan Kusuma; Rudy Badrudin (Universitas Islam Indonesia, 2016)
This study aims to determine the effect of fiscal decentralization on economic growth mediated by financial performance in Bali Province. The source of data employed in this study was secondary data from the financial statement of local government in a counties/city in Bali in 2006 to 2014. The data analysis technique employed in this study was Partial Least Square (PLS). The results show that 1) fiscal decentralization was significantly influential on financial performance measured using the financial independence ratio of local government in Bali; 2) fiscal decentralization was significantly influential on financial performance measured using the ratio of conformity in Bali; 3) fiscal decentralization was significantly influential on economic growth in Bali; 4) financial performance measured using the financial independence ratio of local government had no significant effect on economic growth in Bali; and 5) financial performance measured using the ratio of conformity was significantly influential on economic growth in Bali.